Study of operative results of fracture acetabulum in adults - Nishant Pravin Suvagiya; Nimish Bhanuvadan Patel; Parag Manoj Tank; Poojan Vimesh Shah; Dhaval Vanmali Patel (Asian Journal of Medical Sciences, 2023)
Background: Acetabular fractures are relatively rare intra-articular fractures and due to its complex anatomy, require absolute stability in the form of articular reduction and rigid fixation. Specific approaches need to be taken to operate such fractures and planned protocol needs to be followed to mobilize those patients postoperatively. Aims and Objectives: Primary objective of the study is to analyze the operative results of fracture acetabulum in terms of the operative technique used, clinico-radiological outcome, post-operative range of motion achieved, and time taken for mobilization. Secondary objective is to estimate early and late complication encountered related to technique, implants and to compare our study to other published studies. Materials and Methods: This study is a retrospective study of 26 patients with acetabular fractures operated at our institute from the period of May 2019 to May 2022. All patients who gave consent have been included in our study. Results: There was an improvement in functional and radiological outcomes of all the patients. Twenty-four patients showed excellent to good according to the Merle’d Aubigne Postel scoring in our study. Twenty-five patients achieved excellent to good according to Harris hip score. About 90% of patients in our study returned to their pre fracture work in 4 months. Conclusion: The quality of reduction and fixation is strongly associated with clinical results. In acetabular surgery, for fixing the fracture if we follow established protocols we can get good to excellent outcome in patients.